2011
DOI: 10.1074/jbc.m110.172916
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Excision Repair by Mutant Xeroderma Pigmentosum Group A (XPA) Proteins with Deficiency in Interaction with RPA

Abstract: The xeroderma pigmentosum group A protein (XPA) is a core component of nucleotide excision repair (NER). To coordinate early stage NER, XPA interacts with various proteins, including replication protein A (RPA), ERCC1, DDB2, and TFIIH, in addition to UV-damaged or chemical carcinogendamaged DNA. In this study, we investigated the effects of mutations in the RPA binding regions of XPA on XPA function in NER. XPA binds through an N-terminal region to the middle subunit (RPA32) of the RPA heterotrimer and through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…A recent study has shown that a truncated XPA form with an N-terminal deletion of 29 amino acid residues reduces the binding to RPA32 protein but retains the interaction to RPA heterotrimer. However, compared with the wild-type protein, this truncated XPA form exhibits much lower DNA incision activity in cell-free NER assay, suggesting that the interaction of XPA and RPA32 is critical for NER repair [31]. Another interesting study has demonstrated that XPA can be acetylated at residues Lys63 and Lys67 [32], and deacetylation of XPA by SIRT1 promotes the interaction of XPA and RPA32.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that a truncated XPA form with an N-terminal deletion of 29 amino acid residues reduces the binding to RPA32 protein but retains the interaction to RPA heterotrimer. However, compared with the wild-type protein, this truncated XPA form exhibits much lower DNA incision activity in cell-free NER assay, suggesting that the interaction of XPA and RPA32 is critical for NER repair [31]. Another interesting study has demonstrated that XPA can be acetylated at residues Lys63 and Lys67 [32], and deacetylation of XPA by SIRT1 promotes the interaction of XPA and RPA32.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, essential interactions between RPA and NER proteins are unaffected by hyperphosphorylation of RPA (see above) (Oakley, et al, 2003;Patrick, et al, 2005). Many of these repair proteins are capable of interacting with the unphosphorylated C-terminus of RPA2 rather than the Nterminus of RPA1, which may explain the separation of functions between unphosphorylated and hyperphosphorylated RPA (Ali, et al, 2010;Saijo, et al, 2011). Regardless of the mechanism, this demonstrates the versatility of RPA in DNA metabolism.…”
Section: Interactive Role Of Rpa and Ssb In The Recovery Of Stalled Rmentioning
confidence: 93%
“…Nucleotide excision repair (NER) processes remove helixdistorting lesions by excising a patch of DNA, followed by re-synthesis. In this case, RPA physically interacts with the NER mediator XPA to direct incision to the damaged strand, and to help prevent excessive incision events, which could lead to further degradation of the genome (Krasikova, et al, 2010;Overmeer, et al, 2011;Saijo, et al, 2011). In mismatch repair (MMR), RPA and SSB interact with the exonuclease EXO1 to stimulate excision processes, as well as ensure correct excision termination (Genschel & Modrich, 2009;Lu & Keck, 2008).…”
Section: Interactive Role Of Rpa and Ssb In Ner Ber And Mmrmentioning
confidence: 99%
“…The complex is dynamic, and XPA enters the complex to help scaffold the cycle of repair proteins that enter and leave during the DNA repair process (15,37,38). One of the components of the complex that helps anchor XPA to DNA is the RPA trimer (39,40). As the RASSF1A SNP variant appeared to promote the retention of XPA in the nucleus after UV treatment, we wondered whether the SNPexpressing cells might demonstrate changes in the association of XPA with RPA.…”
Section: Rassf1a Forms a Dna Damage-regulated Complex With Xpamentioning
confidence: 99%